Evaluación del comportamiento de un motor de encendido provocado al emplear diferentes mezclas gasolina – etanol, modificando el grado de temperatura de las bujías. - Salinas León, Pablo Israel (2025)
The growing environmental concern, the continuous increase of greenhouse gas (GHG) emissions and the implementation of stricter regulations regarding emissions have increased the interest in the use of alternative fuels such as ethanol. In this context, the main objective of this research is to evaluate the performance of a spark ignition engine using different gasoline-ethanol blends (E0, E5, E10 and E15), and to explore how the thermal grade of the spark plugs at 25%, 50% and 75% load conditions may be able to influence its performance. An experimental methodology was applied on a dyno to evaluate the performance of a 2006 model year Peugeot 206 engine in which key parameters such as power, torque, specific fuel consumption and pollutant emissions (CO, CO2, HC) were measured. In addition, the physicochemical properties of the blends were analyzed, considering aspects such as octane number (RON) and lower calorific value (LCv). The results reveal that increasing the ethanol content in the blend improves engine torque, power and reduces certain pollutant emissions such as carbon monoxide and hydrocarbons, and an increase in carbon dioxide emissions was observed due to more complete combustion. The thermal grade of the spark plugs also affects engine performance and pollutant emissions. Finally, it can be highlighted that ethanol blends, combined with the proper selection of the thermal grade of the spark plugs, can favor a better efficiency as well as a lower environmental impact.